Phase IV adaptive randomised clinical trials evaluating efficacy and cost-efficacy of pre-emptive pharmacogenetic genotyping strategies in the Spanish National Health System: iPHARMGx Master Protocol and PREVESTATGx nested clinical trial - Xandra García-González; Alberto M Borobia; Antonio J Carcas; Miriam Estébanez; Montserrat Carmona; Irene García García; Francisco Abad-Santos; Luis A López-Fernández; Esther Cubo; Iñaki Imaz-Iglesia; Alicia Marín-Candón; Miriam Saiz-Rodríguez; et al. (BMJ Open)
Introduction Genetic variations impact drug response, driving the need for personalised medicine through pre-emptive pharmacogenetic testing. However, the adoption of pre-emptive pharmacogenetic testing for commonly prescribed drugs, such as statins, outside of tertiary hospitals is limited due to a lack of pharmacoeconomic evidence to support widespread implementation by healthcare policy-makers. The Spanish Consortium for the Implementation of Pharmacogenetics (iPHARMGx Consortium) addresses this by developing a clinical trial master protocol that will govern multiple nested adaptive clinical trials that compare genotype-guided treatments to standard care in specific drug–gene–population triads, asses their cost-efficacy and identify novel biomarkers through advanced sequencing techniques. The first of these studies aims to assess whether a pre-emptive statin therapy genotyping scheme reduces the incidence of statin-associated muscle symptoms (SAMS) in a population at risk of cardiovascular disease susceptible of receiving high-intensity or moderate-intensity doses of statins: The PREVESTATGx trial.Methods and analysis the PREVESTATGX trial is a multicentre, adaptive randomised controlled pragmatic phase IV clinical trial nested to the iPHARMGx master protocol with two parallel arms, aiming for superiority. Randomisation will be conducted on an individual basis with a centralised approach and stratification by centre. After inclusion in the trial and genotyping has been performed, subjects will be randomly allocated to experimental group (pharmacogenetic genotype-guided statin prescription) or standard-of-care statin prescription (as deemed by attending physician). The main objective is to assess the efficacy of a statin pre-emptive genotyping strategy in reducing the incidence of SAMS. A total of 225 subjects will be recruited among the 10 participating centres if no futility/efficacy boundary is reached in the prespecified interim analyses. Recruitment will be carried out during a 12-month period and subjects will be followed for a 9-month period.Ethics and dissemination The PREVESTATGx trial received ethical approval on 24 April 2024. Results will be disseminated via publication in peer-reviewed journals as well as presentation at international conferences. Trial results will be submitted for publication in an open-access peer-reviewed medical speciality-specific publication.Trial registration number EU CT number: 2023-509418-12-00/Clinical trial Identifier (ClinicalTrials.gov): NCT06262685. Protocol version 1.2 12 April 2024 (includes non-substantial modification number 14 June 2024). Trial registration of this study can be located at both the EU Clinical Trials Register available from https:// euclinicaltrials.eu/search-for-clinical-trials/?lang=en and https://clinicaltrials.gov. Registration on both websites was done before the enrolment of the first patient complying with European regulations. EU Clinical Trials Register is a primary registry according to the WHO.